Research on correction coefficient of relationship formula of shearer parameters and coal rock hardness - YANG Jianjian; LI Xu; FU Shichen; WU Miao (Gong-kuang zidonghua, 2015)
In view of problem that current shearer on fully-mechanized coal mining face ca't automatically and accurately identify coal petrography character, the paper analyzed relationship formula between cutting motor parameters and Protodyaknove's coefficient reflecting coal and rock hardness, and obtained that they were approximately proportional and have linear relationship. Value range of correction coefficient was obtained by measured data, and finally it was validated by practical application that the Protodyaknove's coefficient inferred according to correction coefficient was consistent with the actual situation.